Dynamics and Viability of a Small, Estuarine-Resident Population of Lahille’s Bottlenose Dolphins From Southern Brazil - Pedro F. Fruet; Pedro F. Fruet; Pedro F. Fruet; Pedro F. Fruet; Pedro F. Fruet; Luciana M. Möller; Luciana M. Möller; Eduardo R. Secchi; Eduardo R. Secchi (Frontiers in Marine Science, 2021)
Identifying threatened populations and quantifying their vulnerability is crucial for establishing priorities for conservation and providing robust information for decision-making. Lahille’s bottlenose dolphins have been long subjected to by-catch mortality in gillnet fisheries in coastal waters of southern Brazil, particularly in the Patos Lagoon estuary (PLE) and adjacent coastal waters, where dolphins from three populations (or Management Units) show overlapping home ranges. In this study we used a stage-classified matrix population model to conduct a demographic analysis of the PLE’s population with life-history data estimated through an 8 years mark-recapture study. A population viability analysis (PVA) was used to run a series of simulations where the risk was assessed under different by-catch scenarios, taking into account the effects of parameter uncertainty and stochasticity in the projections. In the absence of by-catch, we estimated that this dolphin population would growth at a rate of about 3% annually (95% CI: 1.2–5.8%). Under current by-catch rates, prognoses indicated high probabilities of viability over the next 60 years. These optimistic prognoses appear to be associated with the high survival of adult females. However, the eventual removal of very few mature females (one every year or two) would result in a prominent likelihood of decline from its current abundance at all pre-specified levels. The viability of the population would be substantially improved if the survival of juveniles/sub-adults could be increased. This may be achieved through the recently implemented dolphin protection area, which prohibits gillnet fisheries in the core area of this population. If the protection area reduces the entanglement rates of the most impacted life-stages (i.e., juvenile/sub-adult dolphins), there would be a substantial chance of the PLE’s dolphin population increasing above 20% of its current size, which is here proposed as conservation goal. If met, this goal has the potential to promote habitat quality, increase genetic diversity and connectivity with adjacent populations, enhancing the ability of bottlenose dolphins in southern Brazil to cope with environmental change and potential disease outbreaks.